Guest

The equation having – 3 as a solution is: (a) x + 3 =1 (b) 8 + 2x = 3 (c) 10 + 3x = 1 (d) 2x + 1 = 3

 The equation having – 3 as a solution is: (a) x + 3 =1 (b) 8 + 2x = 3 (c) 10 + 3x = 1 (d) 2x + 1 = 3

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
one year ago
Dear Student

Option (c) is correct here
Consider the equation 10 + 3x = 1.
Transpose 10 to right hand side then it becomes -10

3x = 1–10
x = -9/3
x = -3

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free